Estudo de vida em fadiga de parafusos pediculares revestidos com hidroxiapatita - Larrubia, Davis Machado (2013)
The search for new materials or changes in the manufacture process for the surgical implant companies have been considered one the most challenging issues for the engineering in order to supply high performance products and minimize the damage to the post-operated patient, reducing the recovery time through the improved acceptance and stability of the organism regarding the implanted medical device. Alternatives for the decrease in the time to reach the arthodesis can be obtained through the Surface Treatment technique. The possible use of bioceramics with coating in metallic parts, may increase the bone growth rate of the deposited bioceramic when the adequate parameters are used, although the thermal spray process may impact the fatigue life. This study intends to analyses the life of dynamic loading of a Pedicular Fixation System with the presence of a coated hydroxyapatite film deposited on the surface of the screws through the Flame Spray technique, using a methodology in according with the prescribed by the preface of the standard ASTM F 1717 (Standard Test Methods for Spinal Implant Constructs in a Vertebrectomy Model). The mechanical properties of the coating were found satisfactory, although changes in the coating process are required in order to reach the correct Ca/P ratio.